Penerapan Model Discovery Learning Dengan Pendekatan Teaching at The Right Level Untuk Meningkatkan Diskusi Kelas dan Hasil Belajar Peserta Didik: Application of the Discovery Learning Model with a Teaching at the Right Level Approach to Improve Class Discussions and Student Learning Outcomes - Irma Al-ihsan U, Wa; Djam’an, Nurwati; Rahim, Irmayana (Jurnal Education, 2025)
The objective of this study was to enhance classroom discourse and student achievement by employing the Discovery Learning model integrated with the Teaching at the Right Level (TaRL) approach. The research was carried out in Class XI Technical Computer Network 01 at SMK Negeri 3, involving 30 students. This classroom action research comprised four phases: planning, implementation, observation, and evaluation-reflection. The study spanned two cycles, each consisting of two meetings. Data was collected using classroom discussion observation sheets and achievement tests. The findings revealed a notable improvement in both classroom discussions and student achievement from the first to the second cycle, increasing from 55.4% to 80.3%. Additionally, the number of students who met the learning objectives rose from 12 to 25. Consequently, these results support the conclusion that the integration of Discovery Learning and TaRL can effectively elevate classroom discourse and student learning outcomes.